An application of the modified decomposition method for two dimensional sine-Gordon equation - Kaya, D (Elsevier Science Inc, 2004)
In this study, the decomposition method for solving two dimensional sine-Gordon equation has been implemented. By using a number of initial values, the explicit and numerical solutions of the equation are calculated. The present method performs extremely well in terms of numerical accuracy and efficiency. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: the decomposition method; the modified decomposition method; two dimensional sine-Gordon equation